The complete AJAX fundamentals course. (Packt Publishing, 2022)
Become a pro at AJAX and learn about streams, promises, event loops, and more About This Video Become a full-stack developer by knowing how to send data to a server, listen for a response, and do something with the data Learn JSON and XML data formats and how you can use them with AJAX Discover a depth of knowledge to boost your ability and confidence In Detail AJAX refers to how browsers make HTTP requests to servers asynchronously, listen for results, and then do something with the data when it is received. AJAX is about speed and efficiency. Understanding web development is an ongoing process. To give you a foot up, this course has gone all out to structure an all-encompassing, focused, AJAX course, which will be delivered to you in a way that will benefit you the most. Knowing AJAX is crucial if you want to become a full-stack developer, as it will allow you to make server requests and listen for incoming data asynchronously. It has been noted that AJAX can get tricky at times, and I do not dispute this, but with correct training, which includes explaining the fundamentals in a simple way, you will learn to master and love AJAX. If you want to become a full-stack web developer, you need to know about AJAX and that is what this course is all about. This course takes you through the history of AJAX, HTTP protocol, and the role of AJAX. You will also explore HTTP/2 and HTTP/3, synchronous and asynchronous code. This course will also take you through the basics of AJAX, JSON, XML, and constructor functions. Lastly, you will learn modern AJAX such as fetch basics and streams. By the end of the course, you will become a pro in AJAX fundamentals. Audience This course is for everybody, from beginners and advanced coders. This course is for someone wanting to be an informed professional, an expert, and confident in the entire front-end development process when it comes to sending data to servers and doing something with the response. You only need to know a little HTML and JavaScript.